The effects of moisturisers's physico-chemical properties on customers preference towards foreign and local products - Hazreena, Hamzah (2012)
Moisturisers are colloidal in nature involving water globules microscopically dispersed throughout an oily medium. Modem chemical process industries utilize high shear mixing technology to create novel colloids which can produce an even better product. The long-term stability of particular colloid is great importance in a number of industries such as cosmetic and pharmaceutical. The objectives of this research are to conduct a survey on facial m'oisturiser and on customer's preception, to characterise the physiochemical properties of different moisturiser and to determine the relationship between customer preferences to the physiochemical properties of moisturiser. The compositions of four bands, being two local brands and two foreign brands, of moisturiser have been collated and compared. These moisturisers contain a variety of ingredients, which make them exhibit necessary properties. It was found that the ingredient of local moisturiser differs from that of foreign brand. A survey has been done to determine the preferences in choosing a moisturiser among student Universiti Malaysia Pahang. The perception and product testing surveys found that preferences for international product were slightly higher than that for local products. The stabilities of the moisturiser were studied using thermal gravimetric analysis (TGA). Weight losses with time when the sample was exposed at fixed low temperature and and weight losses due to temperature increase from 30 °C to 200 °C at 10 °C/min were studied. Based on the weight loss profile, sample A and B were found to be most stable, D slightly less stable than B while sample C were the most unstable. However it was also observed that sample A tends be unstable at 45 °C. Base on the TGA result sample A and B were fould to be more stable under normal condition in which the moisturiser may be used. It can be concluded that the preferered product tend to be more stable. Hence the advantage of foreign brand moisturiser is that it tend to be made up of colloid that are more stable than that of the local branded moisturiser.